2001
DOI: 10.1182/blood.v97.2.565
|View full text |Cite
|
Sign up to set email alerts
|

Altered T-cell receptor + CD28-mediated signaling and blocked cell cycle progression in interleukin 10 and transforming growth factor-β–treated alloreactive T cells that do not induce graft-versus-host disease

Abstract: The induction of anergy in T cells, although widely accepted as critical for the maintenance of tolerance, is still poorly understood at the molecular level. Recent evidence demonstrates that in addition to blockade of costimulation using monoclonal antibodies (mAbs) directed against cell surface determinants, treatment of mixed lymphocyte reaction (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…TGF-b has been found to down-regulate ZAP-70 phosphorylation by activation of the protein tyrosine phosphatase SHP-1 [34,35], and therefore it is possible that hCDR1-induced up-regulation in TGF-b reinforced the action of hCDR1 and contributed to the observed down-regulation of TCR signaling. Moreover, similarly to the in vivo treatment with hCDR1, incubation of 16/6Id-immunized murine T cells with TGF-b significantly up-regulated Foxj1 and Foxo3a expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-b has been found to down-regulate ZAP-70 phosphorylation by activation of the protein tyrosine phosphatase SHP-1 [34,35], and therefore it is possible that hCDR1-induced up-regulation in TGF-b reinforced the action of hCDR1 and contributed to the observed down-regulation of TCR signaling. Moreover, similarly to the in vivo treatment with hCDR1, incubation of 16/6Id-immunized murine T cells with TGF-b significantly up-regulated Foxj1 and Foxo3a expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…67 Via its effects on Cdk2, roscovitine has been shown to reduce human alloreactive responses without impairing key responses to tumor (WT-1) or viral (cytomegalovirus, Epstein-Barr virus) antigens. 68 Furthermore, defective activation of Cdk2 (along with Cdk4 and 6) has been associated with tolerance induced by IL-10 and transforming growth factor b 69 and with a reduction in experimental GVHD. 32 These data notwithstanding, the administration of roscovitine at the dose and schedule delivered did effectivity abrogate Cdk5 activity and, consistent with a previous report, 32 was associated with a reduction in clinical GVHD and preservation of GVL effects (Figure 7).…”
Section: /2cmentioning
confidence: 99%
“…It has been previously shown that alloantigen-specific human T cells rendered anergic by lack of costimulation through CD28 are arrested at the G 1 phase of the cell cycle (24). Moreover, alloreactive mouse T cell clones that have been rendered tolerant by CD40 blockade or TGF-␤1/ IL-10 treatment and do not induce GvHD in vivo fail to progress into the late G 1 phase and to enter the S phase of the cell cycle (21,24,25,36). Our findings indicate that VIP-tolerant T cells are cell cycle arrested (Fig.…”
Section: Vip-tolerant T Cells Are Arrested In G 1 Phase and Fail To Pmentioning
confidence: 99%